2007
DOI: 10.1007/s11664-006-0062-8
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanisms and Crack Propagation Paths in Thermally Aged Pb-Free Solder Interconnects

Abstract: Studies were conducted on Pb-free solder interconnects after aging for up to 1,000 h at temperatures of up to 150°C and submitting to drop testing. Cracks were shown to propagate along interphase boundaries (bulk solder/Cu 6 Sn 5 , Cu 6 Sn 5 /Cu 3 Sn, Cu 3 Sn/Cu, and bulk solder/Ag 3 Sn) and along the bulk solder. Intergranular propagation in the solder was rarely observed, although cross sectioning showed evidence of that particular path. There is a transition in preferred crack propagation with aging time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…However, it is known that these intermetallics are brittle. Excessive and large primary intermetallics may deteriorate the solder joint strength depending on the location [52]. Large primary intermetallics located near the solder joint surface may create a weak point and a crack may be initiated.…”
Section: Fabrication Methods Of Reinforced Soldersmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it is known that these intermetallics are brittle. Excessive and large primary intermetallics may deteriorate the solder joint strength depending on the location [52]. Large primary intermetallics located near the solder joint surface may create a weak point and a crack may be initiated.…”
Section: Fabrication Methods Of Reinforced Soldersmentioning
confidence: 99%
“…In the study of failure mechanisms of solder joints, Wang et al [53] and Monlevade at al. [52] indicate that large intermetallics, which includes the primary and interfacial intermetallic compound layer, could promote crack initiation in solder joints. Xian et al [54] report that primary Cu6Sn5 formation in the bulk solder is shown to be affected by the increasing Cu content of the liquid due to the Cu dissolution, the change in phase equilibria and the degree of undercooling for β-Sn.…”
Section: Fabrication Methods Of Reinforced Soldersmentioning
confidence: 99%
See 3 more Smart Citations